The Driver of Green Purchase Intention: Environmental Responsibility, Spirituality, and Social Influence - Mokhamad Agus Firmansyah; Yessy Artanti (Journal of Business and Management Review, 2022)
The development of technology is slowly starting to change human life. With the development of technology, it has an impact on the environment so there is an imbalance in the environment in the world. Many countries are experiencing environmental problems that occur due to technological developments such as the destruction of natural ecosystems and the environment. As a result of this impact, consumers began to change their consumption behavior patterns by intending to buy environmentally friendly products. Environmentally friendly products are products that are safe to use and have a low impact on the environment. The purchase intention of environmentally friendly products or the purchase intention of green is influenced by several factors including the drive for environmental responsibility, spirituality, and social influence. This study aims to analyze and discuss the influence of drive for environmental responsibility, spirituality and social influence on green purchase intentions. This study aims to analyze and discuss the influence of environmental responsibility, spirituality, and social influence on green purchase intentions. This study uses non-probability sampling by relying on judgment to target respondents. Respondents are consumers who care about the environment or who are familiar with environmentally friendly products with an age range of 18-40 years as many as 200 respondents. Multiple linear regression is the technical analysis used in this study. The results of this study indicate that the drive for environmental responsibility, spirituality and social influence has a significant effect on green purchase intentions